Primary stability of a shoulderless Zweymüller hip stem: a comparative in vitro micromotion study. Issue 1 (December 2016) - Bieger, Ralf; Freitag, Tobias; Ignatius, Anita; Reichel, Heiko; Dürselen, Lutz
Abstract Background The Zweymüller stem design has proven long-term stability with a 20-year survival rate of over 90 %. Primary stability necessitates implant-bone micromotions below 150 μm, otherwise bony ingrowth is negatively influenced. Methods Using fresh paired human femurs, we investigated a modification of the Zweymüller-type stem design with reduced proximal lateral shoulder in reference to primary stability. Relative motion between the implant and the cortical bone as well as the irreversible implant migration was investigated under dynamic loading (100–1600 N) over 100, 000 cycles using miniature displacement transducers. Results Micromotions were below the critical threshold for both implants at all measurement points. Axial reversible and irreversible micromotions were not influenced by reducing the shoulder of the prosthesis. Resistance against rotational moments was less pronounced after reduction of the shoulder without statistical significant results. Conclusions Reducing the proximal shoulder of the Zweymüller-type stem design does not negatively influence axial stability but might negatively influence rotational stability. Even though, comparable results still suggest a reasonable resistance against rotational forces.